Business Feasibility Study of the Production of a Simple Digital Distance Measuring Device Based on a Microcontroller - Mubarok, Iman; Purwanda, Eka (Universitas Indo Global Mandiri, 2025)
This simple digital distance measuring device based on a microcontroller was developed as an innovative solution to meet the growing demand for efficient, accurate, and low-power measurement tools. The increasing need for flexible and practical instruments underlies this project. Conventional devices are often considered inefficient or inaccurate in certain applications, especially in confined or hard-to-reach areas. Therefore, a new approach is needed that integrates modern technology into a compact, portable, and economical system. The device uses an Arduino Uno microcontroller as the main controller, combined with an HC-SR04 ultrasonic sensor to detect and measure distance in real time. This combination allows for reliable operation with a low margin of error and fast response. The prototype was tested in various environmental conditions, both indoors and outdoors, under different lighting levels. Results showed consistent performance and accuracy, proving its technical feasibility. Additionally, the device’s low energy consumption makes it suitable for portable use with limited power sources. Beyond technical development, this study includes a business feasibility analysis, covering market potential, production, environmental impact, and financial viability. The findings suggest that this product is not only technically sound but also economically feasible for small- to medium-scale production. With wide potential applications in industrial, educational, and research settings, this device presents itself as an affordable, efficient, and practical digital distance measurement solution. Keywords: business feasibility; digital measuring tool; microcontroller; technology innovation.